2019
DOI: 10.1016/j.ijhydene.2018.02.175
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the long-term stability of the polymer of intrinsic microporosity PIM-1 for hydrogen storage applications

Abstract: Polymers of intrinsic microporosity, such as PIM-1, advantageously combine high surface areas with good processability, which are attractive properties for hydrogen storage applications. Here we address the lack of data on the long-term mechanical stability and hydrogen uptake capacity of PIM-1 in a study carried out over 400 days. Our results show that most mechanical and surface properties of PIM-1 remain stable over this time. In particular, the mechanical strength and elasticity are maintained, and the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Repeated measurements at different points of the sample result in a narrow distribution ofYoung's modulus around the average value. The value of the fresh sample (dark blue) is in good agreement with the data available in the literature from different techniques (1 -1.7 GPa)32,35,52,53…”
supporting
confidence: 88%
“…Repeated measurements at different points of the sample result in a narrow distribution ofYoung's modulus around the average value. The value of the fresh sample (dark blue) is in good agreement with the data available in the literature from different techniques (1 -1.7 GPa)32,35,52,53…”
supporting
confidence: 88%
“…The high performance of PIM-1 has led to additional studies including aging and high pressures. For example, in a recent study Rochat et al demonstrated that PIM-1 is stable over 400 days, showing only modest loss of hydrogen storage capacity, from 2.60 wt % (77 K/100 bar) on day 1 to 1.90 wt % on day 400 [76].…”
Section: Highly Porous Organic Polymers For H2 Storagementioning
confidence: 99%
“…The introduction of additional high surface area nanoporous fillers into PIM-1 provides composites with enhanced performance in terms of surface area, porosity and gas adsorption capacity, while retaining processability and flexibility. It has also been reported that additives in PIM-based composites improve their long term structural stability (Low et al 2018;Rochat et al 2018).…”
mentioning
confidence: 96%